The impact of Digital Textbooks on Digital Literacy in Secondary Education in Sri Lanka - Prabhashini, Kumesh (Annual Research Conference, Department of Sinhala, University of Colombo, 2022)
Senior secondary education counted GCE O/L and GCE A/L grades in Sri Lanka. The country started implementing digital technology in the late 1980s. The concept of a Digital textbook is beneficial in terms of replacing a heavy school- bag, carrying on the learning process after school, and enhancing distance and self-learning. Etextbooks were introduced into the Sri Lankan school system in 2009 as a move toward updating and enhancing the school curriculum. The transition of literature from text to hypertext can be identified as digital literature. E-books are the current format for books and they produce Electronic literature in Audiobooks and PDF format. This research was exploring the impact of Digital Textbooks on Digital literacy in Secondary Education in Sri Lanka. This study used a survey method and 325 senior secondary students in Western Province and used it as a sample of this survey. SPSS software was used for analysing the data and finally came to the conclusion. Due to technological limitations, a preference for reading only printed books, Internet vulnerabilities, and an inability to read screens, digital textbooks are not widely used. It is clear from this sample that digital textbooks have a lack of impact on students' perceptions of digital literacy in Secondary Education in Sri Lanka.
Keywords: Digital Literacy; Digital Textbooks; Senior Secondary Education; Sri Lankan Education; School Curriculum